A project-based view of urban dynamics: analyzing ‘leapfrogging’ and fringe development in Israel - Fulman, Nir; Grinblat, Yulia; Benenson, Itzhak (Cities, 2024)
Analyzing urban pattern dynamics based on construction projects, we classify them into three types - infilling, fringe, and leapfrogging, and focus on the role of leapfrogging projects as seeds for new developments, leading to uncontrolled urban sprawl. To study the leapfrogging phenomenon, we investigate the sprawl of three Israeli cities - Netanya, Haifa, and Safed over 54 years from 1964 to 2018 and conduct a country-wide analysis of the urban sprawl of all 66 Israeli municipalities between 2013 and 2018. Our analysis is based on a country-wide GIS database of roads, buildings, other infrastructure elements, and development plans, as well as high-resolution aerial photos covering the investigated areas and periods. We uncover and characterize a positive feedback mechanism of rapid leapfrogging developments that attract further developments in their proximity and emphasize the potential of leapfrogging development to force divergence from statutory development plans.